If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -4 = 3z + 2 Reorder the terms: -4 + 3z = 3z + 2 Reorder the terms: -4 + 3z = 2 + 3z Add '-3z' to each side of the equation. -4 + 3z + -3z = 2 + 3z + -3z Combine like terms: 3z + -3z = 0 -4 + 0 = 2 + 3z + -3z -4 = 2 + 3z + -3z Combine like terms: 3z + -3z = 0 -4 = 2 + 0 -4 = 2 Solving -4 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -20y=da | | a+198=2(x+7)(x-3) | | 2x^4-16x^2+30=0 | | a+120=2(x+7)(x-3) | | -5x^2+9x+2=0 | | 5x-2=26-2x | | -18=-2n | | 6(2-t)-(3-4t)=4 | | 5(x+8)=2(x+6) | | 5(x-8)=2(x+6) | | -4=3x | | 2x-18=9x+2 | | 7p-11=-3p+7 | | -(7y+1)-(-6y-6)=-2 | | 4(x+1)+2(x+6)=3 | | 7n+24=32 | | 7n-24=42 | | 3x-45=889 | | 8(3x+7)=2(12x+5) | | 3x-9999= | | 345-23+889x= | | 8+2n-2=8n+6-4n | | 7-24=42 | | 3x-23= | | 2r+18r=140 | | 5x^3-20x^2-5x+20=0 | | -9(2b+1)+(19b-6)=0 | | 4.3q-2.3-3.8q=-0.5q-3.3 | | 5x+10y=8 | | -5y+7=-6y+2 | | (0.288)(1-2x)=4x^3 | | 3x-7-2x^2=0 |